Marx’s Critique of Hegel as Part of the Effort to Escape from Metaphysics - Nietlong, Joseph; Kato, Gideon (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Nietzsche and Marx each criticized Hegel from an allegedly post-metaphysical perspective as part of the effort to “escape” from metaphysics. This study settles on Marx, and considers answering the following questions about his thought: is it possible to “escape” from metaphysics in a way he suggests? Are his criticisms of Hegel persuasive? What is at stake in his critique of Hegel?